Late-onset hearing loss was not observed among preschool- aged children with prenatal Zika virus exposure: An analysis of the Microcephaly Epidemic Research Group Pediatric Cohort (2015-2019). - Danielle Seabra Ramos; Lilian Ferreira Muniz; Mariana de Carvalho Leal; Demócrito de Barros Miranda Filho; Ricardo Arraes de Alencar Ximenes; Elizabeth Brickley; Thalia Velho Barreto de Araujo; Celina Maria Turchi Martelli; Silvio da Silva Caldas Neto (PLoS Neglected Tropical Diseases)
Zika virus (ZIKV) infection during pregnancy can lead to Congenital Zika Syndrome (CZS), with significant impacts on early childhood development. This study aimed to analyze the natural history of hearing loss in children with CZS during their first four years of life. Data were collected from the Microcephaly Epidemic Research Group Pediatric Cohort in Pernambuco, Brazil. We investigated whether children with prenatal ZIKV exposure could develop late-onset hearing loss and whether those with preserved auditory thresholds at birth might exhibit deficits in functional hearing or primary language development.The study included children with suspected or confirmed prenatal ZIKV exposure who had normal neonatal hearing screenings. Follow-up assessments included auditory brainstem response testing and behavioral observational audiometry. Children were evaluated every six months up to 24 months of age and annually thereafter until 48 months. Results indicated that late-onset sensorineural hearing loss (SNHL) was not observed in children with prenatal ZIKV exposure and normal neonatal hearing screening. The hearing losses identified were transient and typically related to middle ear effusion. Therefore, our findings reinforce that congenital SNHL associated with ZIKV exposure predominantly manifests at birth, with no evidence supporting its late onset in the first years of life.